Chronic heart failure in patients with nonalcoholic fatty liver disease: prevalence, clinical features, and relevance. Issue 9 (September 2018) - Zhang, Zichuan; Wang, Peize; Guo, Fei; Liu, Xinmin; Luo, Taiyang; Guan, Yang; Chen, Hui; Wang, Zhanhong; Zhao, L; Ma, Xiaohai; Lv, Qiang; Zhang, Yin; et al.
Objective: This study was performed to assess the prevalence of nonalcoholic fatty liver (NAFL) in patients with symptomatic congestive heart failure (CHF) and compare the clinical features with those of patients without NAFL. Methods: In total, 102 patients with CHF were divided into NAFL and non-NAFL groups according to their hepatic ultrasonography findings. All patients underwent transthoracic echocardiography and cardiac magnetic resonance examination. Follow-up was performed for major cardiovascular events (MACE) and readmission due to heart failure at 1, 3, 6, and 12 months after the index hospitalization. Results: NAFL was detected in 37 of 102 patients (36.27%). Compared with the non-NAFL group, patients with NAFL were younger, had a higher body mass index and left ventricular (LV) mass index, and had more severe fibrosis. MACE and readmission occurred in 15 patients in the NAFL group and 29 patients in the non-NAFL group, without a significant difference. Linear regression analysis revealed that after adjusting for confounders, NAFL was independently associated with the LV fibrosis size and the ratio of the LV fibrosis size to the LV mass index. Conclusions: NAFL is present in more than one-third of patients with CHF and is associated with the severity of LV fibrosis.